Financial exclusion of asylum seekers in South Africa and its impact on tax collection - Ndlovu, Bongani (University of the Witwatersrand, Johannesburg, 2024)
This study aimed to explore the extent of financial exclusion in South Africa and its implicationson tax collection and economic growth. Using a cross-sectional research design, quantitative andqualitative data were collected to comprehensively understand the issue. A purposive samplingtechnique was employed to select participants, particularly asylum seekers running informalbusinesses in South Africa, operating without documentation, and not paying taxes whilebenefiting from South African social services. Interviews provided qualitative insights into thefactors contributing to financial exclusion and potential strategies for improvement.The study investigated the challenges experienced by entrepreneurial asylum seekers in accessingformal banking services and obtaining financial products, such as loans or insurance. Additionally,it explored the awareness and understanding of tax obligations among this specific group and theirexperiences in meeting these obligations. By examining the perspectives of tax officials andpolicymakers, the study elucidated the effects of financial exclusion on tax collection andidentified possible solutions.The findings of this research contributed to both academic and practical knowledge. Understandingthe extent of financial exclusion in South Africa and its impact on tax collection and economicgrowth informed policy recommendations and interventions aimed at improving financialinclusion and tax compliance. The study also highlighted the importance of providing financialeducation and support to the unbanked to enhance their understanding of tax obligations. Inconclusion, this research aimed to address the critical issue of financial exclusion with a specificfocus on entrepreneurial asylum seekers in South Africa and its implications on tax collection andeconomic growth. By examining the experiences and perspectives of multiple stakeholders, thisstudy laid out valuable insights into the challenges faced by asylum seekers and contributed to the4development of inclusive policies and practices that promote financial inclusion and enhance taxcollection efficiency
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: FINANCIAL EXCLUSION; ASYLUM SEEKERS; SDG-8: Decent work and economic growth